Determinants of stunting in children aged 24-59 months: a case- control study - Muliani, Muliani; Tondong, Henrietta Imelda; Lewa, Abd Farid; Mutmainnah, Mutmainnah; Maineny, Arie; Asrawaty, Asrawaty (International Journal of Public Health Science (IJPHS), 2023)
Stunting is a sign of persistent malnutrition during a critical period of child development, especially in the second trimester of pregnancy. This study aimed to determine the causes of stunting in infants between 24 and 59 months. The Kamaipura Health Center in Sigi Regency, Indonesia is the location for the research. Data was collected from January to December 2020 from medical record data. The population consisted of 156 children under the age of five, of which 134 samples were selected using a purposive sampling technique and were divided into two groups: stunting and non-stunting. Analytic test using Chi-square, OR, and logistic regression (p=0.05). Infants who are not exclusively breastfed have a 9.44 times higher risk of stunting (OR=9.44; 95% CI=4.28 to 20.7), according to an analysis with a CI of -95%. Chronic energy deficiency and low birth weight during pregnancy are associated with an increased risk of growth disorders by 5.98 (OR=5.98; 95% CI=2.47 to 14.43) and 4.6 times (OR=4.6) respectively; 95% CI=1.73 to 12.42). In addition, the R-square logistic regression analysis of 0.374 indicates that the overall influence of the variables is 37.4%. A history of exclusive breastfeeding, low birth weight (LBW) babies, and chronic energy deficiency (CED) during pregnancy is strongly associated with the prevalence of stunting. To reduce the prevalence of poor growth, better health promotion is needed from the beginning of pregnancy.